Optimization of nitrogen scheduling for higher productivity in machine transplanted rice (Oryza sativa L.) in southern zone of telangana - A.MADHAVI, GHANSHAM PAYMAN, P. RAGHU RAMI REDDY, A SRINIVAS, N REDDY and (The Journal of Research, PJTSAU, 2017)
A field experiment was conducted at Agriculture Research Institiute (ARI), Rajendranagar, Hyderabad, Telangana on aÂ clay loam soil during the kharif seasons of 2014 and 2015 to study the â€œOptimization of nitrogen scheduling for higher productivityÂ in machine transplanted rice (Oryzasativa L.) in southern zone of Telanganaâ€. Experiment was taken up in a split plot design withthree nitrogen levels (120, 160 and 200 kg N ha-1) were kept as main plot treatments and three split schedules (2 equal splits atÂ active tillering and panicle initiation, 3 equal splits at initial tillering, active tillering and panicle initiation and 4 equal splits at initialÂ tillering, active tillering, tillering and panicle initiation) as sub plot treatments with three replications using the long duration varietyÂ BPT 5204. Application of 200 kg N ha-1gave significantly higher number of panicles m-2 (395), panicle length (21.7cm), filled grainsÂ panicle-1 (237.0), grain yield (6,119 kg ha-1) and straw yield (8,597 kg ha-1) over 120 kg N ha-1and was at par with application of 160Â kg N ha-1. Three equal split applications recorded maximum panicles m-2(382), grain (6,028 kg ha-1) and straw (8,164 kg ha-1) yield.Â Combination of 200 kg N ha-1 applied at 3 equal split recorded highest grain yield, net returns and B:C ratio and was at par with 160Â kg N ha-1 applied in 3 equal splits.